The Application Progress of Mobile Healthcare in Drug Management for Elderly Patients with Comorbidities - Lu, Liufang; Lu, Liuyu; Wang, Zhihao; He, Wanxia; Wang, Qiaona; Wei, Yanfen; Ma, Xinling (Journal of Contemporary Medical Practice, 2025)
This article reviews the application forms, effects, existing problems and suggestions of various mobile medical services at home and abroad in the drug management of elderly patients with comorbidities, with the aim of providing a theoretical basis and practical reference for the better implementation of mobile medical services in the drug management of elderly patients with comorbidities.